Объяснение:
3)
воспользуемся формулой (x-y)(x²+xy+y²)=x³ - y³
(a - 5)(a^2 + 5a + 25)= (a - 5)(a^2 + a·5 + 5^2)= a³ - 5³= a³ - 125
О т в е т: b) a^3 - 125
4)
воспользуемся формулой a² - b²=(a-b)(a+b)
(x+3)^2 - (x-3)^2=(x+3+x-3)(x+3-x+3)=2x·6=12x
О т в е т: c) 12x
Объяснение:
3)
воспользуемся формулой (x-y)(x²+xy+y²)=x³ - y³
(a - 5)(a^2 + 5a + 25)= (a - 5)(a^2 + a·5 + 5^2)= a³ - 5³= a³ - 125
О т в е т: b) a^3 - 125
4)
воспользуемся формулой a² - b²=(a-b)(a+b)
(x+3)^2 - (x-3)^2=(x+3+x-3)(x+3-x+3)=2x·6=12x
О т в е т: c) 12x